ANALISIS WAKAF POLIS ASURANSI PERSPEKTIF HUKUM EKONOMI SYARI’AH DALAM PENGENTASAN PROBLEMATIKA UMAT - Luayyin, Reza Hilmy; M. Nabat Ardli; Moh. Arifin (JSE: Jurnal Sharia Economica, 2023)
The concept of waqf also reflects the values of social care and sustainability in Islam. "Waqf of insurance policies" refers to the act of allocating the benefits or proceeds from an insurance policy for charitable or public benefit purposes. In this context, "insurance policy" refers to an insurance contract that involves the payment of premiums to an insurance company in order to obtain financial protection from certain risks, such as property damage, health, or other unforeseen events. This means that some or all of the benefits derived from insurance claims will be allocated for charitable or social benefit purposes, such as helping people in need, supporting education, or building public facilities. The waqf of insurance policies is an innovation to explore the potential of wealth so that it can be empowered more optimally as much as possible for greater benefits and also solve the problems of the people. This paper uses a qualitative approach and normative juridical methods as well as related literature. The results showed (1) Its existence can certainly open up greater opportunities to be able to grow the economic potential of the people so that it can be empowered for the general benefit and be able to solve various kinds of economic problems of the people. (2) Waqf of sharia insurance policies is part of a breakthrough in waqf management in exploring the economic potential of the people to distribute wealth effectively and on target. The synergy of naẓir, government, or related institutions is needed in the management, supervision, and development of waqf so that waqf assets remain productive, trustworthy, and truly useful to overcome the problems of the people, especially in the real sector. (3) Some of the main functions of waqf insurance policies in overcoming people's problems are for 1) Social Welfare such as hospitals, schools, orphanages, and mosques, which provide benefits to the community as a whole 2) Educational Development such as establishing schools, colleges, or training centers, which provide access to quality education to the community, even future generations. 3) Economic Empowerment such as creating jobs, developing skills, and improving the local economy. For example, waqf can be directed to establish micro or medium enterprises that provide economic benefits to the community. 4) Health Care such as establishing hospitals or health centers financed from waqf proceeds. 5) Religious Development such as building and maintaining places of worship such as mosques,ṡallâ, or other religious institutions. 6) Public Benefit such as developing infrastructure, recreational areas, and other public facilities. 7) Social and Spiritual Growth such as improving the socio-religious of the community.